THE CHARACTER VALUE OF RESPECT AMONG LOWER-GRADE STUDENTS AT SD NEGERI 2 BENDUNGAN, GONDANG, TULUNGAGUNG ACADEMIC YEAR 2025/2026 - Nourma Oktaviarini (STKIP PGRI TULUNGAGUNG, 2025)
The character value of respect among students encompasses the values of affection, humility, honesty, and tolerance. The implementation of respect character values among students has been carried out effectively, as evidenced by students’ ability to demonstrate indicators of respectful character. This study aims to describe the implementation of respect character values among lower-grade students at SD Negeri 2 Bendungan. This research employed a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation. The results showed that the average implementation of respect character values among lower-grade students was categorized as good, with the following percentages: honorific aspect 91%, appreciation 84%, respectfulness 70%, friendliness 83%, harmony 89%, politeness 78%, and manners 88%. The conclusions are as follows: (1) honorific—students use polite language when communicating with others; (2) appreciation—students respect and accept differences; (3) respectfulness—students demonstrate respect by valuing others’ actions; (4) friendliness—students display friendly behavior toward others; (5) harmony—students maintain peaceful relationships with peers to avoid conflict; (6) politeness—students behave politely toward friends and others; and (7) manners—students demonstrate proper etiquette and comply with school rules